Anti-dazzle full-ultraviolet-proof optical protection material and preparation method thereof
Through the design of multi-layer structure and specific raw materials, anti-glare fully anti-UV optical protection materials are prepared, which solves the problem of single function of the existing automobile window film and achieves multi-functional optical protection effects.
Patent Information
- Application Number
- CN202510553049.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2025-08-01
AI Technical Summary
The existing automotive window film has a single function and cannot meet consumers' needs for multifunctional performance such as ultraviolet, infrared barrier, anti-glare, explosion-proof, etc.
A multi-layer structure consisting of a scratch-resistant hardening layer, a PET film layer, a composite adhesive layer, a PET film layer and an mounting adhesive layer is adopted. Through specific raw materials composition and process design, anti-glare fully anti-ultraviolet optical protection materials are prepared, including the introduction of silicone modified polyurethane acrylate and nanosilica in the scratch-resistant hardening layer, cesium tungsten bronze and epoxy resin in the composite adhesive layer, and silicone modified polyurethane acrylate in the mounting adhesive layer to improve the protection performance of the material.
It realizes multifunctional optical protection materials with anti-glare, fully anti-ultraviolet rays, excellent infrared barrier properties, and explosion-proof, which improves the service life and safety of the materials.
Smart Images

Figure CN120396490A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of optical protection materials, and specifically relates to an anti-glare and fully anti-ultraviolet optical protection material and a preparation method thereof. Background Art
[0002] With the progress of technology and the improvement of people's material living standards, more and more cars have entered people's lives, and the accessories of cars have also developed vigorously. Automotive window film is a multi-layer polyester composite optical protection material, mostly composed of a PET film (polyethylene terephthalate film) and an acrylate pressure-sensitive adhesive, which is pasted on the surface of automotive glass to make it have functions such as heat insulation, heat preservation, privacy protection, and safety protection.
[0003] The functions of existing automotive window films are relatively single and cannot meet the growing needs of consumers, such as the requirements for multi-functional properties such as anti-ultraviolet, infrared blocking, anti-glare, and explosion-proof. Summary of the Invention
[0004] The purpose of the present invention is to provide an anti-glare and fully anti-ultraviolet optical protection material and a preparation method thereof to solve the problems raised in the prior art.
[0005] To achieve the above purpose, the present invention provides the following technical solutions:
[0006] An anti-glare and fully anti-ultraviolet optical protection material is composed of a scratch-resistant hardening layer, a PET film layer a, a composite adhesive layer, a PET film layer b, an installation adhesive layer, and a PET release film layer from top to bottom in sequence;
[0007] The raw material composition of the scratch-resistant hardening layer is: organosilicon-modified polyurethane acrylate, colorant, reactive diluent, leveling agent, photoinitiator, solvent, modified nano-silica;
[0008] The raw material composition of the composite adhesive layer is: cesium tungsten bronze, epoxy resin, acrylic acid, organosilicon-modified polyurethane acrylate, bisphenol A ethoxylate dimethacrylate, photoinitiator;
[0009] The raw material composition of the installation adhesive layer is: organosilicon-modified polyurethane acrylate, epoxy resin, acrylic acid, bisphenol A ethoxylate dimethacrylate, photoinitiator, modified nano-silica.
[0010] Furthermore, the thickness of the scratch-resistant hardening layer is 1 - 2 μm, the thickness of the PET film layer a is 19 - 50 μm, the thickness of the composite adhesive layer is 7 - 10 μm, the thickness of the PET film layer b is 23 - 50 μm, and the thickness of the installation adhesive layer is 7 - 12 μm.
[0011] Further, the reactive diluent is obtained by mixing trimethylolpropane triacrylate and pentaerythritol tetraacrylate in a mass ratio of 1:2.
[0012] Further, based on parts by mass, the raw material composition of the scratch-resistant hardening layer is: 15-19 parts of organosilicon-modified polyurethane acrylate, 1-2 parts of colorant, 1-3 parts of reactive diluent, 0.2-0.5 parts of leveling agent, 0.6-1 part of photoinitiator, 20-30 parts of solvent, and 1-3 parts of modified nano-silica.
[0013] Further, based on parts by mass, the raw material composition of the composite adhesive layer is: 16-22 parts of epoxy resin, 3-5 parts of acrylic acid, 3-5 parts of organosilicon-modified polyurethane acrylate, 1-3 parts of bisphenol A ethoxylate dimethacrylate, 1-3 parts of cesium tungsten bronze, and 0.7-1.2 parts of photoinitiator.
[0014] Further, in the mounting adhesive layer, the mass ratio of organosilicon-modified polyurethane acrylate to epoxy resin is 1:3, and in the mounting adhesive layer, the mass ratio of epoxy resin, acrylic acid, bisphenol A ethoxylate dimethacrylate, photoinitiator, and modified nano-silica is 75:3:5:3.5:4.
[0015] Further, the preparation of the organosilicon-modified polyurethane acrylate includes the following steps:
[0016] (1) Mix δ-decalactone, p-xylene glycol, and diphenyl phosphate, stir at 18-25 °C for 11-12 h, add acetone, wash 3-5 times with potassium hydroxide solution, add ethyl acetate, wash 3-5 times with deionized water, and rotary evaporate to obtain polycaprolactone diol with a hydrophobic side chain;
[0017] (2) Under a nitrogen atmosphere, mix hydroxyl-terminated polydimethylsiloxane, polycaprolactone diol with a hydrophobic side chain, dibutyltin dilaurate, and p-methoxyphenol, heat to 58-60 °C, add isophorone diisocyanate, heat to 78-82 °C and hold for 2-3 h, add pentaerythritol triacrylate and a chalcone derivative containing a double bond to obtain the organosilicon-modified polyurethane acrylate.
[0018] Further, the preparation of the modified nano-silica includes the following steps:
[0019] 1) Mix absolute ethanol, tetrabutyl titanate, and glacial acetic acid, add a mixed solution of absolute ethanol and deionized water, add nano-silica, ultrasonically stir for 20-30 min, transfer to a reaction kettle, hold at 195-205 °C for 110-130 min, cool, wash, dry, and grind to obtain composite nano-silica;
[0020] 2) Mix ethanol, deionized water, and composite nano-silica, adjust the pH value to 3.9 - 4.1, ultrasonically disperse for 5 - 10 min, add (3-mercaptopropyl)trimethoxysilane, keep warm at 78 - 82 °C for 11 - 12 h, centrifuge, wash, and dry to obtain mercapto-functionalized composite nano-silica;
[0021] 3) Under a nitrogen atmosphere, mix mercapto-functionalized composite nano-silica and ethyl acetate, add a chalcone derivative containing a double bond and 1-hydroxycyclohexyl phenyl ketone, heat up to 60 - 70 °C, and irradiate with ultraviolet light with a wavelength of 365 nm for 1 - 2 h to obtain modified nano-silica.
[0022] Further, the preparation of the chalcone derivative containing a double bond includes the following steps:
[0023] Mix 4-allyloxybenzaldehyde, p-hydroxyacetophenone, and absolute ethanol, stir at 18 - 25 °C, add sodium hydroxide solution, continue to stir for 6 - 7 h, adjust the pH to 2, filter, wash, and dry to obtain the chalcone derivative containing a double bond.
[0024] Further, a preparation method of an anti-glare and fully anti-ultraviolet optical protection material includes the following steps:
[0025] S1: Mix organosilicon-modified polyurethane acrylate, colorant, reactive diluent, leveling agent, photoinitiator, solvent, and modified nano-silica to prepare a scratch-resistant and hardening coating solution; coat the scratch-resistant and hardening coating solution on the upper surface of PET film layer a and cure it by light to form a scratch-resistant and hardening layer;
[0026] S2: Mix cesium tungsten bronze, epoxy resin, acrylic acid, organosilicon-modified polyurethane acrylate, bisphenol A ethoxylate dimethacrylate, and photoinitiator to prepare a composite adhesive solution; composite the lower surface of PET film layer a and the upper surface of PET film layer b with the composite adhesive solution and cure it by light to form a composite adhesive layer;
[0027] S3: Mix organosilicon-modified polyurethane acrylate, epoxy resin, acrylic acid, bisphenol A ethoxylate dimethacrylate, photoinitiator, and modified nano-silica to obtain a mounting adhesive solution; use the mounting adhesive solution to composite the lower surface of PET film layer b and the PET release film layer and cure it by light to form a mounting adhesive layer, thus obtaining an anti-glare and fully anti-ultraviolet optical protection material.
[0028] Compared with the prior art, the beneficial effects of the present invention are:
[0029] The present invention provides an anti-glare and fully anti-UV optical protection material and a preparation method thereof. Through process and composition design, it is composed of a scratch-resistant hardening layer, a PET film layer a, a composite adhesive layer, a PET film layer b, a mounting adhesive layer, and a PET release film layer from top to bottom in sequence, and a multi-layer composite multi-functional optical protection material with excellent anti-glare property, full anti-UV property, infrared barrier property, and explosion-proof property is prepared.
[0030] To endow the optical protection material with colorfulness, different colorants are introduced into its scratch-resistant hardening layer to achieve a colorful effect; to endow the optical protection material with excellent water resistance, scratch resistance, fingerprint resistance, and anti-glare property, organosilicon-modified polyurethane acrylate, colorant, reactive diluent, leveling agent, photoinitiator, solvent, and modified nano-silica are mixed to prepare a photocurable scratch-resistant hardening coating solution, which is coated on the surface of the PET film layer a to construct the scratch-resistant hardening layer.
[0031] In line with the green production route, the present invention uses decanolide derived from Cryptocarya massoy as a bio-based raw material. Through ring-opening of the hydroxyl group, a bio-based polycaprolactone diol containing a hydrophobic side chain is obtained, which is introduced into the preparation of polyurethane acrylate together with hydroxyl-terminated polydimethylsiloxane as hydroxyl components. Using a chalcone derivative containing a double bond and pentaerythritol triacrylate as capping agents, a hydrophobic organosilicon-modified polyurethane acrylate is obtained. A chalcone derivative containing a double bond is introduced into it to endow the organosilicon-modified polyurethane acrylate with excellent anti-UV property, and the chalcone derivative is prepared from 4-allyloxybenzaldehyde and p-hydroxyacetophenone as raw materials.
[0032] To improve the anti-glare property and anti-UV property of the scratch-resistant hardening layer, nano-titanium dioxide and nano-silica are introduced as fillers for the scratch-resistant hardening layer. To improve the uniformity of the dispersion of the fillers in the scratch-resistant hardening layer, first, a hydrothermal method is used with titanium butoxide and nano-silica as raw materials to prepare composite nano-silica, and then it is mercapto-functionalized using a silane coupling agent (3-mercaptopropyl) trimethoxysilane, and then a chalcone derivative containing a double bond is grafted using a photo-click reaction to improve the binding strength between the nano-silica and the base material of the scratch-resistant hardening solution, and endow the scratch-resistant hardening layer with excellent mechanical strength, anti-glare property, and anti-UV property.
[0033] To endow the optical material with excellent infrared barrier property and heat insulation property, cesium tungsten bronze is introduced as a filler into the composite adhesive layer. To improve the adhesion and water resistance of the composite adhesive solution, epoxy resin is used as the base material, and organosilicon-modified polyurethane acrylate is introduced as the water-resistant component, acrylic acid is used as the tackifying resin, and bisphenol A ethoxylate dimethacrylate is used as the diluent; in the mounting adhesive layer, by controlling the raw material ratio, a photocurable pressure-sensitive adhesive with high initial tack, good adhesion and excellent ultraviolet resistance is prepared, and then a PET release film that plays a role in protection and winding is laminated. Through component and structure design, excellent explosion-proof safety is imparted to the optical protection material, thereby constructing a multifunctional optical protection material and greatly improving the service life of the optical protection material. Brief Description of the Drawings
[0034] Figure 1 It is a schematic structural diagram of the optical protection material prepared in Examples 1-3; 1-Scratch-resistant hardening layer, 2-PET film layer a, 3-Composite adhesive layer, 4-PET film layer b, 5-Mounting adhesive layer, 6-PET release film layer. Detailed Description of the Embodiments
[0035] Next, the technical solutions in the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts belong to the scope of protection of the present invention.
[0036] It should be noted that if there are directional indications such as up, down, left, right, front, and back in the embodiments of the present invention, the directional indications are only used to explain the relative positional relationship and movement conditions between components in a specific posture. If this specific posture changes, the directional indications will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the fact that those of ordinary skill in the art can implement them. When the combination of technical solutions results in contradictions or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0037] The technical solutions of the present invention are further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0038] Example 1: A preparation method of an anti-glare and fully anti-ultraviolet optical protection material, comprising the following steps:
[0039] S1: Mix silicone-modified polyurethane acrylate, colorant, reactive diluent, leveling agent, photoinitiator, solvent, and modified nano-silica to prepare a scratch-resistant and hardening coating solution; coat the scratch-resistant and hardening coating solution on the upper surface of PET film layer a2 and cure it by light to form a scratch-resistant and hardening layer 1;
[0040] S2: Mix cesium tungsten bronze, epoxy resin, acrylic acid, silicone-modified polyurethane acrylate, bisphenol A ethoxylate dimethacrylate, and photoinitiator to prepare a composite adhesive solution; use the composite adhesive solution to composite the lower surface of PET film layer a2 with the upper surface of PET film layer b4 and cure it by light to form a composite adhesive layer 3;
[0041] S3: Mix silicone-modified polyurethane acrylate, epoxy resin, acrylic acid, bisphenol A ethoxylate dimethacrylate, photoinitiator, and modified nano-silica to obtain an installation adhesive solution; use the installation adhesive solution to composite the lower surface of PET film layer b4 with PET release film layer 6 and cure it by light to form an installation adhesive layer 3, thus obtaining an anti-glare and fully anti-UV optical protection material;
[0042] The thickness of the scratch-resistant and hardening layer 1 is 1 μm; the thickness of PET film layer a2 is 19 μm, the thickness of composite adhesive layer 3 is 7 μm, the thickness of PET film layer b4 is 23 μm, and the thickness of installation adhesive layer 5 is 7 μm;
[0043] By mass, the raw material composition of the scratch-resistant and hardening layer 1 is: 15 parts of silicone-modified polyurethane acrylate, 1 part of colorant, 1 part of reactive diluent, 0.2 part of leveling agent, 0.6 part of photoinitiator, 20 parts of solvent, and 1 part of modified nano-silica;
[0044] By mass, the raw material composition of the composite adhesive layer 3 is: 16 parts of epoxy resin, 3 parts of acrylic acid, 3 parts of silicone-modified polyurethane acrylate, 1 part of bisphenol A ethoxylate dimethacrylate, 1 part of cesium tungsten bronze, and 0.7 part of photoinitiator;
[0045] In the installation adhesive layer 5, the mass ratio of silicone-modified polyurethane acrylate to epoxy resin is 1:3, and in the installation adhesive layer 5, the mass ratio of epoxy resin, acrylic acid, bisphenol A ethoxylate dimethacrylate, photoinitiator, and modified nano-silica is 75:3:5:3.5:4;
[0046] The reactive diluent is a compound obtained by mixing trimethylolpropane triacrylate and pentaerythritol tetraacrylate in a mass ratio of 1:2;
[0047] The preparation of the silicone-modified polyurethane acrylate includes the following steps:
[0048] (1) Mix 3.4 g of δ - decanolide, 0.7 g of p - xylyl alcohol, and 0.25 g of diphenyl phosphate, stir at 18 °C for 12 h, add 50 mL of acetone, wash 3 times with 1 mg / mL potassium hydroxide solution, add 50 mL of ethyl acetate, wash 3 times with deionized water, and perform rotary evaporation to obtain polycaprolactone diol with a hydrophobic side chain;
[0049] (2) Under a nitrogen atmosphere, mix 2.5 g of hydroxyl - terminated polydimethylsiloxane, 5.2 g of polycaprolactone diol with a hydrophobic side chain, 24 mg of dibutyltin dilaurate, and 48 mg of p - hydroxyanisole, heat to 58 °C, add 16 g of isophorone diisocyanate, heat to 78 °C and keep warm for 3 h, then add 3.1 g of pentaerythritol triacrylate and 2.3 g of chalcone derivative containing a double bond to obtain organosilicon - modified polyurethane acrylate;
[0050] The preparation of the modified nano - silica includes the following steps:
[0051] 1) Mix 20 mL of absolute ethanol, 10 mL of tetrabutyl titanate, and 1.8 mL of glacial acetic acid, add a mixture of 20 mL of absolute ethanol and 2 mL of deionized water, add 2 g of nano - silica, stir ultrasonically for 20 min, transfer to a reaction kettle, keep warm at 195 °C for 130 min, cool, wash, dry, and grind to obtain composite nano - silica;
[0052] 2) Mix 60 mL of ethanol, 20 mL of deionized water, and 0.5 g of composite nano - silica, adjust the pH value to 3.9, disperse ultrasonically for 5 min, add 2 mL of (3 - mercaptopropyl) trimethoxysilane, keep warm at 78 °C for 12 h, centrifuge, wash, and dry to obtain mercapto - functionalized composite nano - silica;
[0053] 3) Under a nitrogen atmosphere, mix 2.5 g of mercapto - functionalized composite nano - silica and 20 mL of ethyl acetate, add 1.8 g of chalcone derivative containing a double bond and 43 mg of 1 - hydroxycyclohexyl phenyl ketone, heat to 60 °C, and irradiate with ultraviolet light with a wavelength of 365 nm for 1 h to obtain modified nano - silica;
[0054] The preparation of the chalcone derivative containing a double bond includes the following steps:
[0055] Mix 0.8 g of 4 - allyloxybenzaldehyde, 0.7 g of p - hydroxyacetophenone, and 5 mL of absolute ethanol, stir at 18 °C, add 5 mL of 3 mol / L sodium hydroxide solution, continue to stir for 6 h, adjust the pH to 2, filter, wash, and dry to obtain the chalcone derivative containing a double bond.
[0056] Example 2: A preparation method of an anti - glare and fully anti - ultraviolet optical protection material includes the following steps:
[0057] S1: Mix organosilicon-modified polyurethane acrylate, colorant, reactive diluent, leveling agent, photoinitiator, solvent, and modified nano-silica to prepare a scratch-resistant and hardening coating solution; coat the scratch-resistant and hardening coating solution on the upper surface of PET film layer a2 and cure it by light to form a scratch-resistant and hardening layer 1;
[0058] S2: Mix cesium tungsten bronze, epoxy resin, acrylic acid, organosilicon-modified polyurethane acrylate, bisphenol A ethoxylate dimethacrylate, and photoinitiator to prepare a composite adhesive solution; use the composite adhesive solution to composite the lower surface of PET film layer a2 and the upper surface of PET film layer b4 and cure it by light to form a composite adhesive layer 3;
[0059] S3: Mix organosilicon-modified polyurethane acrylate, epoxy resin, acrylic acid, bisphenol A ethoxylate dimethacrylate, photoinitiator, and modified nano-silica to obtain an installation adhesive solution; use the installation adhesive solution to composite the lower surface of PET film layer b4 and PET release film layer 6 and cure it by light to form an installation adhesive layer 3, and obtain an anti-glare and fully anti-ultraviolet optical protection material;
[0060] The thickness of the scratch-resistant and hardening layer 1 is 1 μm; the thickness of PET film layer a2 is 19 μm, the thickness of the composite adhesive layer 3 is 7 μm, the thickness of PET film layer b4 is 23 μm, and the thickness of the installation adhesive layer 5 is 7 μm;
[0061] By mass, the raw material composition of the scratch-resistant and hardening layer 1 is: 17 parts of organosilicon-modified polyurethane acrylate, 1.5 parts of colorant, 2 parts of reactive diluent, 0.3 part of leveling agent, 0.8 part of photoinitiator, 25 parts of solvent, and 2 parts of modified nano-silica;
[0062] By mass, the raw material composition of the composite adhesive layer 3 is: 18 parts of epoxy resin, 4 parts of acrylic acid, 4 parts of organosilicon-modified polyurethane acrylate, 2 parts of bisphenol A ethoxylate dimethacrylate, 2 parts of cesium tungsten bronze, and 1 part of photoinitiator;
[0063] In the installation adhesive layer 5, the mass ratio of organosilicon-modified polyurethane acrylate to epoxy resin is 1:3, and in the installation adhesive layer 5, the mass ratio of epoxy resin, acrylic acid, bisphenol A ethoxylate dimethacrylate, photoinitiator, and modified nano-silica is 75:3:5:3.5:4;
[0064] The reactive diluent is a compound obtained by mixing trimethylolpropane triacrylate and pentaerythritol tetraacrylate in a mass ratio of 1:2;
[0065] The preparation of the organosilicon-modified polyurethane acrylate includes the following steps:
[0066] (1) Mix 3.4 g of δ-decalactone, 0.7 g of p-xylene glycol, and 0.25 g of diphenyl phosphate, stir at 20 °C for 11.5 h, add 50 mL of acetone, wash 4 times with 1 mg / mL potassium hydroxide solution, add 50 mL of ethyl acetate, wash 4 times with deionized water, and rotary evaporate to obtain polycaprolactone diol with a hydrophobic side chain;
[0067] (2) Under a nitrogen atmosphere, mix 2.5 g of hydroxyl-terminated polydimethylsiloxane, 5.2 g of polycaprolactone diol with a hydrophobic side chain, 24 mg of dibutyltin dilaurate, and 48 mg of p-hydroxyanisole, heat to 59 °C, add 16 g of isophorone diisocyanate, heat to 80 °C and keep warm for 2.5 h, add 3.1 g of pentaerythritol triacrylate and 2.3 g of chalcone derivative containing double bonds to obtain organosilicon-modified polyurethane acrylate;
[0068] The preparation of the modified nano-silica includes the following steps:
[0069] 1) Mix 20 mL of absolute ethanol, 10 mL of tetrabutyl titanate, and 1.8 mL of glacial acetic acid, add a mixed solution of 20 mL of absolute ethanol and 2 mL of deionized water, add 2 g of nano-silica, ultrasonically stir for 25 min, transfer to a reaction kettle, keep warm at 200 °C for 120 min, cool, wash, dry, and grind to obtain composite nano-silica;
[0070] 2) Mix 60 mL of ethanol, 20 mL of deionized water, and 0.5 g of composite nano-silica, adjust the pH value to 4, ultrasonically disperse for 8 min, add 2 mL of (3-mercaptopropyl)trimethoxysilane, keep warm at 80 °C for 11.5 h, centrifuge, wash, and dry to obtain mercapto-functionalized composite nano-silica;
[0071] 3) Under a nitrogen atmosphere, mix 2.5 g of mercapto-functionalized composite nano-silica and 20 mL of ethyl acetate, add 1.8 g of chalcone derivative containing double bonds and 43 mg of 1-hydroxycyclohexyl phenyl ketone, heat to 65 °C, and irradiate with ultraviolet light with a wavelength of 365 nm for 1.5 h to obtain modified nano-silica;
[0072] The preparation of the chalcone derivative containing double bonds includes the following steps:
[0073] Mix 0.8 g of 4-allyloxybenzaldehyde, 0.7 g of p-hydroxyacetophenone, and 5 mL of absolute ethanol, stir at 20 °C, add 5 mL of 3 mol / L sodium hydroxide solution, continue to stir for 6.5 h, adjust the pH to 2, filter, wash, and dry to obtain the chalcone derivative containing double bonds.
[0074] Example 3: A preparation method of an anti-glare and fully anti-ultraviolet optical protection material includes the following steps:
[0075] S1: Mix silicone - modified polyurethane acrylate, colorant, reactive diluent, leveling agent, photo - initiator, solvent, and modified nano - silica to prepare a scratch - resistant hardening coating solution; coat the scratch - resistant hardening coating solution on the upper surface of PET film layer a2 and cure it by light to form a scratch - resistant hardening layer 1;
[0076] S2: Mix cesium tungsten bronze, epoxy resin, acrylic acid, silicone - modified polyurethane acrylate, bisphenol A ethoxylate dimethacrylate, and photo - initiator to prepare a composite adhesive solution; laminate the lower surface of PET film layer a2 and the upper surface of PET film layer b4 with the composite adhesive solution and cure it by light to form a composite adhesive layer 3;
[0077] S3: Mix silicone - modified polyurethane acrylate, epoxy resin, acrylic acid, bisphenol A ethoxylate dimethacrylate, photo - initiator, and modified nano - silica to obtain an installation adhesive solution; laminate the lower surface of PET film layer b4 and PET release film layer 6 with the installation adhesive solution and cure it by light to form an installation adhesive layer 5, and obtain an anti - glare and fully anti - ultraviolet optical protection material;
[0078] The thickness of the scratch - resistant hardening layer 1 is 1μm; the thickness of PET film layer a2 is 19μm, the thickness of the composite adhesive layer 3 is 7μm, the thickness of PET film layer b4 is 23μm, and the thickness of the installation adhesive layer 5 is 7μm;
[0079] By mass, the raw material composition of the scratch - resistant hardening layer 1 is: 19 parts of silicone - modified polyurethane acrylate, 2 parts of colorant, 3 parts of reactive diluent, 0.5 part of leveling agent, 1 part of photo - initiator, 30 parts of solvent, and 3 parts of modified nano - silica;
[0080] By mass, the raw material composition of the composite adhesive layer 3 is: 22 parts of epoxy resin, 5 parts of acrylic acid, 5 parts of silicone - modified polyurethane acrylate, 3 parts of bisphenol A ethoxylate dimethacrylate, 3 parts of cesium tungsten bronze, and 1.2 parts of photo - initiator;
[0081] In the installation adhesive layer 5, the mass ratio of silicone - modified polyurethane acrylate to epoxy resin is 1:3, and in the installation adhesive layer 5, the mass ratio of epoxy resin, acrylic acid, bisphenol A ethoxylate dimethacrylate, photo - initiator, and modified nano - silica is 75:3:5:3.5:4;
[0082] The reactive diluent is a compound of trimethylolpropane triacrylate and pentaerythritol tetraacrylate in a mass ratio of 1:2;
[0083] The preparation of the silicone - modified polyurethane acrylate includes the following steps:
[0084] (1) Mix 3.4 g of δ - decanolide, 0.7 g of p - benzene dimethanol, and 0.25 g of diphenyl phosphate, stir at 25 °C for 11 h, add 50 mL of acetone, wash 5 times with 1 mg / mL potassium hydroxide solution, add 50 mL of ethyl acetate, wash 5 times with deionized water, and rotary evaporate to obtain polycaprolactone diol with a hydrophobic side chain;
[0085] (2) Under a nitrogen atmosphere, mix 2.5 g of hydroxyl - terminated polydimethylsiloxane, 5.2 g of polycaprolactone diol with a hydrophobic side chain, 24 mg of dibutyltin dilaurate, and 48 mg of p - hydroxyanisole, heat to 60 °C, add 16 g of isophorone diisocyanate, heat to 82 °C and hold for 2 h, then add 3.1 g of pentaerythritol triacrylate and 2.3 g of chalcone derivative containing a double bond to obtain organosilicon - modified polyurethane acrylate;
[0086] The preparation of the modified nano - silica includes the following steps:
[0087] 1) Mix 20 mL of anhydrous ethanol, 10 mL of tetrabutyl titanate, and 1.8 mL of glacial acetic acid, add a mixed solution of 20 mL of anhydrous ethanol and 2 mL of deionized water, add 2 g of nano - silica, ultrasonically stir for 30 min, transfer to a reaction kettle, hold at 205 °C for 110 min, cool, wash, dry, and grind to obtain composite nano - silica;
[0088] 2) Mix 60 mL of ethanol, 20 mL of deionized water, and 0.5 g of composite nano - silica, adjust the pH value to 4.1, ultrasonically disperse for 5 - 10 min, add 2 mL of (3 - mercaptopropyl) trimethoxysilane, hold at 82 °C for 11 h, centrifuge, wash, and dry to obtain mercapto - functionalized composite nano - silica;
[0089] 3) Under a nitrogen atmosphere, mix 2.5 g of mercapto - functionalized composite nano - silica and 20 mL of ethyl acetate, add 1.8 g of chalcone derivative containing a double bond and 43 mg of 1 - hydroxycyclohexyl phenyl ketone, heat to 70 °C, and irradiate with ultraviolet light with a wavelength of 365 nm for 2 h to obtain modified nano - silica;
[0090] The preparation of the chalcone derivative containing a double bond includes the following steps:
[0091] Mix 0.8 g of 4 - allyloxybenzaldehyde, 0.7 g of p - hydroxyacetophenone, and 5 mL of anhydrous ethanol, stir at 25 °C, add 5 mL of 3 mol / L sodium hydroxide solution, continue stirring for 6 h, adjust the pH to 2, filter, wash, and dry to obtain the chalcone derivative containing a double bond.
[0092] Comparative Example 1: Taking Example 3 as the control group, replace the silicone-modified polyurethane acrylate with (hexafunctional polyurethane acrylate 230A2: Hubei Chengfeng Chemical Co., Ltd.), and other processes are normal.
[0093] Comparative Example 2: Taking Example 3 as the control group, replace the modified nano-silica with nano-silica, and other processes are normal.
[0094] The working conditions for photocuring are: put it into a UV curing machine for curing, and the curing energy is 500 mJ / cm 2 .
[0095] Sources of raw materials used (only as demonstration examples):
[0096] PET release film (25 μm): Shenzhen Ruichangxing Technology Co., Ltd.; PET film layer (extruded from DuPont Rynite 530BK503); colorant (black) JS3901: Hubei Jusheng Technology Co., Ltd.; leveling agent 7580: Guangzhou Double Bond Trading Co., Ltd.; cesium tungsten bronze BD4741: Hubei Baidu Chemical Co., Ltd.; p-methoxyphenol (99%): Hubei Qifei Pharmaceutical Chemical Co., Ltd.; epoxy resin 815HC5019: Tianmen Hengchang Chemical Co., Ltd.; acrylic acid A434196, bisphenol A ethoxylate dimethacrylate B477930, trimethylolpropane triacrylate T102522, pentaerythritol tetraacrylate P192936, δ-decalactone D465508, photoinitiator (1-hydroxycyclohexyl phenyl ketone) H110064, p-xylene glycol B107001, diphenyl phosphate D139308, hydroxyl-terminated polydimethylsiloxane P433351, dibutyltin dilaurate D100274, isophorone diisocyanate I109582, pentaerythritol triacrylate P189117, tetrabutyl titanate T104105, nano-silica S104597, (3-mercaptopropyl) trimethoxysilane M100619, 4-allyloxybenzaldehyde A353132, p-hydroxyacetophenone H102969: Aladdin Reagents; acetone, potassium hydroxide, ethyl acetate, ethanol, solvent (methyl isobutyl ketone), glacial acetic acid, analytical pure: reagents of Sinopharm Group.
[0097] Performance test: Test the optical protection materials prepared in the examples and comparative examples:
[0098] Pencil hardness: Tested using a pencil hardness tester with reference to ASTM D3363:2005; UV blocking rate: Tested for the transmittance at 400 nm using a UV-visible spectrophotometer; Infrared shielding property: Tested for the transmittance in the range of 800 - 1100 nm; Water contact angle: Tested using a contact angle measuring instrument with 2 μL deionized water droplets; Salt spray resistance: The sample is placed in a salt spray chamber at a test temperature of 37 °C and a sodium chloride concentration of 6.1 g / L, and the appearance of phenomena such as foaming is observed. It is considered qualified if there are no phenomena after 720 h; The obtained results are shown in Table 1;
[0099] Table 1
[0100]
[0101] The present invention provides an anti-glare and fully UV-blocking optical protection material and its preparation method. Through process and composition design, it is composed of a scratch-resistant hardening layer, a PET film layer a, a composite adhesive layer, a PET film layer b, a mounting adhesive layer, and a PET release film layer from top to bottom in sequence, and a multi-layer composite multi-functional optical protection material with excellent anti-glare property, full UV-blocking property, infrared barrier property, and explosion-proof property is prepared.
[0102] Comparing Example 3 with Comparative Example 1, following the green production route, the present invention uses δ-decalactone derived from Cryptocarya massoy as a bio-based raw material. Through ring-opening of the hydroxyl group, a bio-based polycaprolactone diol containing a hydrophobic side chain is obtained. Together with hydroxyl-terminated polydimethylsiloxane, they are introduced as hydroxyl components into the preparation of polyurethane acrylate. Using a chalcone derivative containing a double bond and pentaerythritol triacrylate as capping agents, a hydrophobic organosilicon-modified polyurethane acrylate is obtained. By introducing a chalcone derivative containing a double bond into it, excellent UV resistance is imparted to the organosilicon-modified polyurethane acrylate, and the chalcone derivative is prepared from 4-allyloxybenzaldehyde and p-hydroxyacetophenone as raw materials.
[0103] Comparing Example 3 with Comparative Example 2, to improve the anti-glare property and UV resistance of the scratch-resistant hardening layer, nano-titanium dioxide and nano-silica are introduced as fillers for the scratch-resistant hardening layer. To improve the uniformity of the dispersion of the fillers in the scratch-resistant hardening layer, first, hydrothermal method is used with tetrabutyl titanate and nano-silica as raw materials to prepare composite nano-silica, and then it is mercapto-functionalized using a silane coupling agent (3-mercaptopropyl) trimethoxysilane. Then, through a photo-click reaction, a chalcone derivative containing a double bond is grafted to improve the bonding strength between the nano-silica and the base material of the scratch-resistant hardening liquid, and excellent mechanical strength, anti-glare property, and UV resistance are imparted to the scratch-resistant hardening layer.
[0104] It is obvious to those skilled in the art that the present invention is not limited to the details of the above-described exemplary embodiments, and that the present invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the present invention. Therefore, from any point of view, the embodiments should be regarded as exemplary and non-limiting. The scope of the present invention is defined by the appended claims rather than the above description. Therefore, all changes falling within the meaning and scope of the equivalent elements of the claims are intended to be embraced within the present invention. Any reference signs in the claims should not be construed as limiting the claims concerned.
Claims
1. An anti-glare and fully anti-ultraviolet optical protection material, characterized in that, It is composed of a scratch-resistant hardening layer (1), a PET film layer a (2), a composite adhesive layer (3), a PET film layer b (4), a mounting adhesive layer (5), and a PET release film layer (6) from top to bottom in sequence; The raw material composition of the scratch-resistant hardening layer (1) is: organosilicon-modified polyurethane acrylate, colorant, reactive diluent, leveling agent, photoinitiator, solvent, modified nano-silica; The raw material composition of the composite adhesive layer (3) is: cesium tungsten bronze, epoxy resin, acrylic acid, organosilicon-modified polyurethane acrylate, bisphenol A ethoxylate dimethacrylate, photoinitiator; The raw material composition of the mounting adhesive layer (5) is: organosilicon-modified polyurethane acrylate, epoxy resin, acrylic acid, bisphenol A ethoxylate dimethacrylate, photoinitiator, modified nano-silica.
2. An anti-glare and fully anti-ultraviolet optical protection material according to claim 1, characterized in that, The thickness of the scratch-resistant hardening layer (1) is 1 - 2 μm, the thickness of the PET film layer a (2) is 19 - 50 μm, the thickness of the composite adhesive layer (3) is 7 - 10 μm, the thickness of the PET film layer b (4) is 23 - 50 μm, and the thickness of the mounting adhesive layer (5) is 7 - 12 μm.
3. An anti-glare and full UV protection optical protection material according to claim 1, characterized in that, The reactive diluent is obtained by mixing trimethylolpropane triacrylate and pentaerythritol tetraacrylate in a mass ratio of 1:
2.
4. An anti-glare and fully anti-ultraviolet optical protection material according to claim 1, characterized in that, By mass parts, the raw material composition of the scratch-resistant hardening layer (1) is: 15 - 19 parts of organosilicon-modified polyurethane acrylate, 1 - 2 parts of colorant, 1 - 3 parts of reactive diluent, 0.2 - 0.5 parts of leveling agent, 0.6 - 1 part of photoinitiator, 20 - 30 parts of solvent, 1 - 3 parts of modified nano-silica.
5. An anti-glare and fully anti-ultraviolet optical protection material according to claim 1, characterized in that, By mass parts, the raw material composition of the composite adhesive layer (3) is: 16 - 22 parts of epoxy resin, 3 - 5 parts of acrylic acid, 3 - 5 parts of organosilicon-modified polyurethane acrylate, 1 - 3 parts of bisphenol A ethoxylate dimethacrylate, 1 - 3 parts of cesium tungsten bronze, 0.7 - 1.2 parts of photoinitiator.
6. An anti-glare and fully anti-ultraviolet optical protection material according to claim 1, characterized in that, In the mounting adhesive layer (5), the mass ratio of organosilicon-modified polyurethane acrylate to epoxy resin is 1:3, and the mass ratio of epoxy resin, acrylic acid, bisphenol A ethoxylate dimethacrylate, photoinitiator, and modified nano-silica in the mounting adhesive layer (5) is 75:3:5:3.5:
4.
7. An anti-glare and full anti-ultraviolet optical protection material according to claim 1, characterized in that, The preparation of the organosilicon-modified polyurethane acrylate includes the following steps: (1) Mix δ-decalactone, p-xylene glycol, and diphenyl phosphate, stir at 18 - 25 °C for 11 - 12 h, add acetone, wash with potassium hydroxide solution 3 - 5 times, add ethyl acetate, wash with deionized water 3 - 5 times, and rotary evaporate to obtain polycaprolactone diol with a hydrophobic side chain; (2) Under a nitrogen atmosphere, mix hydroxyl-terminated polydimethylsiloxane, polycaprolactone diol with a hydrophobic side chain, dibutyltin dilaurate, and p-methoxyphenol, heat to 58 - 60 °C, add isophorone diisocyanate, heat to 78 - 82 °C and keep warm for 2 - 3 h, add pentaerythritol triacrylate and a chalcone derivative containing a double bond to obtain organosilicon-modified polyurethane acrylate.
8. An anti-glare and fully anti-ultraviolet optical protection material according to claim 1, characterized in that, The preparation of the modified nano-silica includes the following steps: 1) Mix absolute ethanol, tetrabutyl titanate, and glacial acetic acid, add the mixed solution of absolute ethanol and deionized water, add nano-silica, stir ultrasonically for 20 - 30 min, transfer to a reaction kettle, keep warm at 195 - 205 °C for 110 - 130 min, cool, wash, dry, and grind to obtain composite nano-silica; 2) Mix ethanol, deionized water, and composite nano-silica, adjust the pH value to 3.9 - 4.1, disperse ultrasonically for 5 - 10 min, add (3-mercaptopropyl)trimethoxysilane, keep warm at 78 - 82 °C for 11 - 12 h, centrifuge, wash, and dry to obtain mercapto-functionalized composite nano-silica; 3) Under a nitrogen atmosphere, mix mercapto-functionalized composite nano-silica and ethyl acetate, add a chalcone derivative containing a double bond and 1-hydroxycyclohexyl phenyl ketone, heat up to 60 - 70 °C, and irradiate with ultraviolet light with a wavelength of 365 nm for 1 - 2 h to obtain modified nano-silica.
9. An anti-glare and full UV-blocking optical protection material according to claim 7 or 8, characterized in that, The preparation of the chalcone derivative containing a double bond includes the following steps: Mix 4-allyloxybenzaldehyde, p-hydroxyacetophenone, and absolute ethanol, stir at 18 - 25 °C, add sodium hydroxide solution, continue to stir for 6 - 7 h, adjust the pH to 2, filter, wash, and dry to obtain the chalcone derivative containing a double bond.
10. The preparation method of an anti-glare and fully anti-ultraviolet optical protection material according to any one of claims 1-8, characterized in that, Include the following steps: S1: Mix organosilicon-modified polyurethane acrylate, pigment, reactive diluent, leveling agent, photoinitiator, solvent, and modified nano-silica to prepare a scratch-resistant hardening coating solution; coat the scratch-resistant hardening coating solution on the upper surface of the PET film layer a(2), and cure by light to form a scratch-resistant hardening layer (1); S2: Mix cesium tungsten bronze, epoxy resin, acrylic acid, organosilicon-modified polyurethane acrylate, bisphenol A ethoxylate dimethacrylate, and photoinitiator to prepare a composite adhesive solution; use the composite adhesive solution to laminate the lower surface of the PET film layer a(2) and the upper surface of the PET film layer b(4), and cure by light to form a composite adhesive layer (3); S3: Mix organosilicon-modified polyurethane acrylate, epoxy resin, acrylic acid, bisphenol A ethoxylate dimethacrylate, photoinitiator, and modified nano-silica to obtain a mounting adhesive solution; use the mounting adhesive solution to laminate the lower surface of the PET film layer b(4) and the PET release film layer (6), and cure by light to form a mounting adhesive layer (3) to obtain an anti-glare and fully anti-UV optical protection material.
Citation Information
Cited By
UV and moisture dual-curing adhesive and preparation process thereof
CN120924221A
Optical film with anti-dazzle self-repairing function
CN122037267A
An optical film with anti-glare and self-healing function
CN122037267B
